2013
DOI: 10.1212/wnl.0b013e3182a43b78
|View full text |Cite
|
Sign up to set email alerts
|

Limbic hyperconnectivity in the vegetative state

Abstract: Objective: To investigate functional connectivity between the default mode network (DMN) and other networks in disorders of consciousness. Methods:We analyzed MRI data from 11 patients in a vegetative state and 7 patients in a minimally conscious state along with age-and sex-matched healthy control subjects. MRI data analysis included nonlinear spatial normalization to compensate for disease-related anatomical distortions. We studied brain connectivity data from resting-state MRI temporal series, combining non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 41 publications
8
56
0
Order By: Relevance
“…DMN resting functional connectivity and size (number of voxels inside the DMN) were significantly reduced in patients with DOC compared with HCs. 16,18,19,21,23,24,30,33,40 Two of these studies exclusively evaluated patients with anoxic brain injury; both demonstrated decreased connectivity within the DMN. 19,30 Studies demonstrated a relationship between the degree of impaired consciousness and DMN connectivity, with greater reductions in connectivity in VS compared with MCS.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
“…DMN resting functional connectivity and size (number of voxels inside the DMN) were significantly reduced in patients with DOC compared with HCs. 16,18,19,21,23,24,30,33,40 Two of these studies exclusively evaluated patients with anoxic brain injury; both demonstrated decreased connectivity within the DMN. 19,30 Studies demonstrated a relationship between the degree of impaired consciousness and DMN connectivity, with greater reductions in connectivity in VS compared with MCS.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
“…3). The effect was greater in patients with VS/UWS than in patients with MCS [37]. This limbic hyperconnectivity may reflect the persistent engagement of residual neural activity in self-reinforcing neural loops which may disrupt normal patterns of connectivity, including synchronized neural activity in DMN.…”
Section: Disorders Of Consciousness and Neural Correlates Of Awarenessmentioning
confidence: 90%
“…This limbic hyperconnectivity may reflect the persistent engagement of residual neural activity in self-reinforcing neural loops which may disrupt normal patterns of connectivity, including synchronized neural activity in DMN. A loss of connectivity is, therefore, not necessarily the global hallmark of impaired consciousness but only an aspect of a multifaceted dysfunction in the architecture of brain connectivity [37]. Correspondingly, patients with complex partial seizures due to temporal lobe epilepsy associated with mesial sclerosis show increased regional synchronization in areas outside the DMN, such as the ipsilateral parahippocampal gyrus, midbrain, insula, corpus callosum, bilateral sensorimotor cortex, and frontoparietal subcortical structures [38].…”
Section: Disorders Of Consciousness and Neural Correlates Of Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…195 The future integration of 'high-tech' brain measurements with existing clinical and behavioural methods of assessment should pave the way for new and innovative applications, and further elucidation of pathophysiological mechanisms could provide new opportunities for restoration of function through interventional neuromodulation. 46,196 These emerging technologies also bring new ethical challenges, and have important implications for medicolegal decision-making. 197 The novel neuroimaging and electrophysiological technologies await large-scale, multicentre validation studies.…”
Section: Discussionmentioning
confidence: 99%